Effect of different carbon sources on L(+)-lactic acid production by Rhizopus oryzae - Bulut, S; Elibol, M; Ozer, D (Elsevier, 2004)
The effect of different carbon sources on lactic acid production by Rhizopus oryzae was studied using glucose, sucrose, beet molasses, carob pod and wheat bran as substrate. The highest lactic acid concentration was obtained when 150 g/l glucose was present in the medium as the sole carbon source. In that case, the lactic acid yield was approximately 60% by weight based on the amount of glucose consumed. Wheat bran was found to be an unsuitable substrate for this particular fermentation. Pasteurisation of molasses increased lactic acid production rate compared to that of untreated molasses. Likewise, 58 g/l lactic acid was obtained by using the supernatant containing sugars extracted from carob pod. This medium could therefore be considered as an alternative carbon source for lactic acid production. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: lactic acid; Rhizopus oryzae; fermentation; glucose; sucrose; carob pod